Synthesis and characterization of an electron-deficient conjugated polymer based on pyridine-flanked diketopyrrolopyrrole. Issue 21 (6th April 2021) - Yang, Jialin; Yang, Li; Chen, Qianqian; Guo, Keke; Han, Ji-Min
Abstract : We report a pyridine-flanked diketopyrrolopyrrole monomer and all-acceptor conjugated polymers synthesized therefrom. Photophysical, thermal and electrochemical properties of the polymers have been determined. Abstract : As classic organic dyes, diketopyrrolopyrrole (DPP) derivatives have attracted researchers' attention due to their high charge carrier mobility and good environmental stability. In our study, the pyridine-flanked diketopyrrolopyrrole (PyDPP) with a large conjugated system and 2, 2′-bithiazole were used to design and synthesize an all-acceptor (A–A) polymer, poly-(dipyridinyldiketopyrrolopyrrole-bithiazole), named P(PyDPP2OD-2Tz). At the same time, poly-(dipyridinyldiketopyrrolopyrrole-bithiophene), P(PyDPP2OD-2T), was synthesized for comparison and discussion. The A–A polymer P(PyDPP2OD-2Tz) synthesized in our research had a highest occupied molecular orbital (HOMO) energy level of −5.85 eV, and a lowest unoccupied molecular orbital (LUMO) energy level of −3.65 eV. Its energy band gap was 2.20 eV, which was similar to P(PyDPP2OD-2T). At the same time, measurement of a series of performance characterizations proved that the polymer P(PyDPP2OD-2Tz) had good thermal stability. It was judged to be an amorphous polymer with a wide distribution of glassy regions. Based on the above advantages, it is expected to increase the carrier mobility of polymer P(PyDPP2OD-2Tz), and improve its device performance as an n-type organic semiconductor material applied to organic field effect transistors, and find new designs for the development of organic functional materials science ideas.